A Systematic Literature Review to Assist in Defining New Guidelines and Practical Handbooks for the Documentation of Built Heritage - Lorenzo Teppati Losè; Fulvio Rinaudo (Heritage)
The documentation of cultural heritage, particularly built heritage, represents a critical component in ensuring its preservation, sustainable management, and effective transmission to future generations. As the field increasingly undergoes a digital transformation, there is a growing need for structured, standardised approaches that can guide professionals and stakeholders through the complexities of documentation practices. Despite the availability of numerous standards and charters, a clear synthesis of consolidated methodologies and recent technological shifts remains limited. This study addresses this gap by conducting a Systematic Literature Review (SLR) to assess current documentation practices. The research is part of a larger initiative funded by the FSE REACT-EU programme under the Italian PON Ricerca e Innovazione 2014–2020, specifically aiming to support public and private stakeholders in developing practical documentation strategies. Using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, over 266 publications were analysed to reconstruct the state of the art. The findings confirm widely adopted practices among research groups while also highlighting emerging trends driven by technological advancements in geomatics. These insights will contribute to the formulation of practical guidelines to support operators in the field and reinforce the integration of innovative tools in Cultural Heritage documentation workflows.